PENERAPAN METODE ISO 9126 DALAM PENGUJIAN KUALITAS SISTEM INFORMASI AKADEMIK SATYA WACANA (SIASAT) UNIVERSITAS KRISTEN SATYA WACANA - Leonardo Ade Pradana Putra; Suprihadi Suprihadi (Program Studi Pendidikan Informatika, Universitas Citra Bangsa, 2023)
The development of information systems has changed human activity, especially education. Universitas Kristen Satya Wacana has made changes by creating a website called SIASAT (Sistem Informasi Akademik Satya Wacana). SIASAT can be accessed by all UKSW communities, features include Student Registration, Course Registration, Study Card, Study Results, lecture schedules, transcripts, student activity, and book borrowing. Previous researchers said SIASAT was still lacking in standardization, so testing was carried out using ISO 9126 with functional and non-functional approaches, containing the characteristics of Functionality, Reliability, Usability, Efficiency, and Portability. The data collection process using Google Forms throughout 132 IT students and interviews with 2019 IT students. The Functional test result scored 80.8%, classified as “good”. Reliability testing can be declared reliable, with a value of 0.874, so exceeds the provision of 0.7. Validity testing results in a table of 0.171